Antimicrobial activity of amazon medicinal plants - Souza Júnior, Paulo Roberto Pires de; Santos, Geyse Souza; Prado, Laryssa dos Santos; Peters, Leila Priscila; Carvalho, Clarice Maia (Acta Scientiarum. Biological Sciences, 2023)
In recent decades, an increase in resistance of bacteria and fungi to antimicrobials has been observed. Therefore, have each other investigated the antimicrobial potential of plants with medicinal properties. In this context, the Amazon has a high variability of plants with potentially active compounds. Thus, the present study aimed to evaluate the antimicrobial activity of ethanol extracts from Amazonian medicinal plants. Leaves and stems of 19 plant species were dried, crushed and extracted by cold maceration with ethanol. The extracts were dried and solubilized at a concentration of 100 mg mL-1 to done antimicrobial activity assays using the agar diffusion method against gram-positive and gram-negative bacteria, and fungi of the genus Candida. Of the total of 38 extracts analyzed, 14 (36.8%) had antimicrobial activity against at least one of the microorganisms tested. The Brazilnut tree stem extract was active against the highest number of microorganisms, three bacteria (S. aureus, E. coli and K. pneumoniae) and three fungi (C. tropicalis, C. parapsilosis and C. krusei). The mulateiro leaf extract was active against three microorganisms, the saracura-mira stem extract against two, and the other extracts only against one microorganism. K. pneumoniae was the most sensitive microorganism, and the most resistant was C. albicans. The lowest values for minimum inhibitory concentration (MIC) for antibacterial activity were for stone-breaker stem extract against K. pneumoniae (0.048 mg mL-1), and for antifungal activity for Brasilnut tree stem against C. krusei (3.125 mg mL-1), stone-breaker leaf against C. guillermondii (3.125 mg mL-1), and mulateiro leaf against C. tropicalis (3.125 mg mL-1). The lowest values of minimum microbicidal concentration (MMC) were for the extracts of stone-breaker stem against K. pneumoniae (0.192 mg mL-1) and mulateiro leaf against C. tropicalis (3.125 mg mL-1). The tested Amazonian medicinal plants had antimicrobial activity, especially Brazilnut tree, this being the first report for this plant species.